Smart House (Rumah Pintar) As Non-Formal Education Implemented in Pamesi Village - Deswarni, Dini; Setiawati (Research and Social Study Institute, 2022)
Pamesi Village is one of the villages in Bengkalis Regency, which is one of the regencies in Bengkalis that consists of several sub-districts. This village is one of the villages where lecturers and students from STAI Hubbulwathan Duri Riau perform community service. The Smart House (Rumah Pintar) program is one of the service programs implemented in this village in an effort to address the issue of education for school-age children in this village, which still lacks educational facilities, particularly for Non-formal education. As a result, this program was implemented in this village through a variety of methods, including the Community Based Research (CBR) and R&D models, as well as outreach and mentoring to school-age children in this village. School-age children in Pamesi Village now have the opportunity to receive Non formal education outside of formal school hours, as well as participate in more positive activities in their spare time. Benefits of having a Smart house to increase interest in English and Arabic and reading also, young people and society, making the library a source of information and knowledge, educating and increasing the ability of the community evenly through library services and optimizing environmental resources in an efficient and effective manner in line with the development of science and technology